Identification and Characterization of NBS Resistance Genes in Akebia trifoliata - Yu, Xiaojiao; Zhong, Shengfu; Yang, Huai; Chen, Chen; Chen, Wei; Yang, Hao; Guan, Ju; Fu, Peng; Tan, Feiquan; Ren, Tianheng; Shen, Jinliang; Zhang, Min; et al. (Frontiers in Plant Science, 2021)
Akebia trifoliata is an important multiuse perennial plant that often suffers attacks from various pathogens due to its long growth cycle, seriously affecting its commercial value. The absence of research on the resistance (R) genes of A. trifoliata has greatly limited progress in the breeding of resistant varieties. Genes encoding proteins containing nucleotide binding sites (NBSs) and C-terminal leucine-rich repeats (LRRs), the largest family of plant resistance (R) genes, are vital for plant disease resistance. A comprehensive genome-wide analysis showed that there were only 73 NBS genes in the A. trifoliata genome, including three main sub families (50 coiled coil (CC)-NBS-LRR (CNL), 19 Toll/interleukin-1 receptor (TIR)-NBS-LRR (TNL) and four resistance to powdery mildew8 (RPW8)-NBS-LRR (RNL) genes). Additionally, 64 mapped NBS candidates were unevenly distributed on 14 chromosomes, most of which were assigned to the chromosome ends; 41 of these genes were located in clusters, and the remaining 23 genes were singletons. Both the CNLs and TNLs were further divided into four subgroups, and the CNLs had fewer exons than the TNLs. Structurally, all eight previously reported conserved motifs were identified in the NBS domains, and both their order and their amino acid sequences exhibited high conservation. Evolutionarily, tandem and dispersed duplications were shown to be the two main forces responsible for NBS expansion, producing 33 and 29 genes, respectively. A transcriptome analysis of three fruit tissues at four developmental stages showed that NBS genes were generally expressed at low levels, while a few of these genes showed relatively high expression during later development in rind tissues. Overall, this research is the first to identify and characterize A. trifoliata NBS genes and is valuable for both the development of new resistant cultivars and the study of molecular mechanisms of resistance.